The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/jmr.609
|View full text |Cite
|
Sign up to set email alerts
|

Recognition promoted by Zn2+ between phenanthroline bridging polyaza ligands and nucleotides — Zn2+ acts as ‘messenger’ between the receptor and substrate

Abstract: The stability constants of the supramolecular complexes formed between L ((a,b,c,d)) or their Zn(2+) complexes, and adenosine 5'-triphosphate (ATP) in aqueous solution were determined by potentiometric titrations (25 degrees C, I = 0.1 mol dm(-3) KNO(3)). The results show that protonated aliphatic-substituted L (a,d) and aromatic-substituted L (b,c) ligands and/or Zn(II) ion can efficiently recognition the substrate, ATP. All of the equilibrium studies, (1)H and (31)P nuclear magnetic resonance spectra indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Many studies that have been made reported that ATP could bind to metal(II) ions with three donor atoms. 9,13,15 The first two of these atoms are the βand γ-phosphate oxygen atoms, and the third atom is the N (7) nitrogen atom in adenine. The stability of the MA complex in the Cu(II):ATP system is very high, whereas the stability of the MAH complex is very low.…”
Section: Binary Complexes Of Atp and Aspartic And Glutamicmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies that have been made reported that ATP could bind to metal(II) ions with three donor atoms. 9,13,15 The first two of these atoms are the βand γ-phosphate oxygen atoms, and the third atom is the N (7) nitrogen atom in adenine. The stability of the MA complex in the Cu(II):ATP system is very high, whereas the stability of the MAH complex is very low.…”
Section: Binary Complexes Of Atp and Aspartic And Glutamicmentioning
confidence: 99%
“…It has been noted that the N(7) nitrogen atom binds to the metal weakly in Zn(II):ATP complexes. 15 The potentiometric titrations of (1:1) and (1:2) M(II):aa systems have been carried out under the same experimental conditions. In the Ni(II):aa Cu(II):aa systems, m 2.0 has been observed as the inflection point (Figures 2 and 3, curve IV).…”
Section: Binary Complexes Of Atp and Aspartic And Glutamicmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress in this area would require new strategies for the selective recognition and subsequent signaling of the event under physiological pH conditions. In previous reported literature, the recognition of adenosine was focused on supramolecular catalysis area at certain pH condition [21,22]. In this paper, we reported the recognition of adenosine in neutral medium.…”
Section: Introductionmentioning
confidence: 95%
“…Nevertheless, a growing body of research work related to anion coordination is now emerging, including the recognition of halides [15][16][17][18][19][20][21][22][23][24][25][26][27], phosphates and nucleotides [5,, nucleic acids [46], carboxylates [21-25, 39, 45, 47-56], nitrates [18-23, 25, 27', 57-60] and sulfates [18-23, 25, 27, 38, 39, 59, 61], mainly by organic receptors. In addition, a number of studies also describe the recognition phenomena between metalloreceptors and anions such as phosphates [32,[62][63][64][65][66][67], carboxylates [67][68][69], nucleic acids [70][71][72][73], nucleobases and nucleotides [74][75][76].…”
Section: Introductionmentioning
confidence: 99%